GEOGRAPHICAL IMPACT ON ESSENTIAL OIL COMPOSITION OF ENDEMIC KUNDMANNIA ANATOLICA HUB.-MOR. (APIACEAE) - Åžanli, Arif; KaradoÄŸan, Tahsin (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Kundmannia anatolica Hub.-Mor. is an endemic specie of Apiaceae diversified in Turkey. Several parts of the plant may contain essential oils in different quantity which can be influenced by environmental factors, mainly altitude. The aim of this study was to test whether there is any altitude effect on volatile chemical constituents of essential oil obtained from the fruits of K. anatolica growing spontaneously in different altitudes of Lakes Region in Turkey. Materials and Methods: K. anatolica was collected in 2015 at different altitudes (400, 820, 1002 and 1560 m) of Lakes Region Turkey. The fruits of the plants were distilled for 3 h using a Clevenger type apparatus according to the British Pharmacopiea (1980). Essential oils of the fruits were collected using hydro distillation method and analyzed by GC–MS/FID. Results: Essential oil contents of fruits increased by corresponding increase in altitude level. Predominant compounds were α-Pinene (27.87-61.94%) and β-Pinene (24.92-36.46%) of the total oil of K. anatolica. Other important compounds were α-Thujene (2.66-8.15%), l-Limonene (1.83-8.23%), α-Phellandrene (1.85-5.01%) and these compounds were higher in low altitudes. Conclusion: Altitude change affected the terpenoid biosynthesis and oxygenated monoterpenes generally and were greatest when low; while sesquiterpene constituents were greatest at high altitudes. The influence of altitude seems to be an important factor for yielding the chemical profile of K. anatolica essential oils. Thus, the location of the plant must be taken into account depending on the intended use.